Iron-doped metal-organic framework with enhanced oxygen evolution reaction activity for overall water splitting. (11th October 2021) - Pan, Yangdan; Zhang, Jianshuo; Zhao, Zhiliang; Shi, Le; Wu, Buke; Zeng, Lin
Abstract: Water electrolysis is an energy conversion technology to provide green and clean hydrogen energy. Developing a high-efficient and durable electrocatalyst is a critical material for water electrolysis. Therefore, we synthesize a series of iron-doped metal-organic frameworks (MOFs) by a facile one-pot hydrothermal method. In the conventional three-electrode-cell, the Co/Fe (1:1)-MOF catalyst exhibits an overpotential of 317 mV at a current density of 10 mA cm −2 in the oxygen evolution reaction (OER). Furthermore, the electrolysis performance of Co/Fe (1:1)-MOF catalyst is further evaluated in a home-made anion-exchange-membrane water electrolysis cell. With the Co/Fe (1:1)-MOF as the OER catalyst and commercial Pt/C as the hydrogen-evolution-reaction catalyst, the cell presents an overpotential of 490 mV at a large current density of 500 mA cm −2, which is superior to the benchmark cell with commercial IrO2 as the OER catalyst in the alkaline media. Theoretical calculation demonstrates that the introduction of Fe dopant into MOFs significantly reduces the binding energy of ∗O and ∗OOH intermedium during the OER progress. Consequently, the electrocatalytic activity is increased, which is perfectly consistent with the experimental results. This work suggests that the iron-doped MOFs structure significantly improves the electrocatalytic activity and provides a facile strategy to produce hydrogen at a large current density for industrial water electrolysis. Highlights: The Co/Fe (1:1)-MOF performs a low overpotential (317 mV at 10 mA cm −2 ) for OER. The AEMWE with Co/Fe (1:1)-MOF shows a low overpotential of 490 mV at 500 mA cm −2 . The DFT shows that the free energy of Co/Fe-MOF is much lower than that of Fe-MOF.